Vibandha; A common Gastrointestinal anomaly that affect Nutritional efficiency in the Children (International Journal of Food and Nutritional Sciences, 2021)
The words Vibandha or Vibaddha or Baddha purisha, which signify one of the states of Srotodusti, particularly in Purishavaha srotas, literally mean Sanga meaning full or partial obstruction of purishvaha Srotas. The distinctive indications of their vitiation include the voiding of a little quantity of faeces with difficulty, a very scybalous stool accompanied by sound and discomfort, and the voiding of a small quantity of faeces with difficulty. All of the signs indicate that vitiated Vata is involved in the pathophysiology of Vibandha. Vibandha is one of the most common clinical diseases characterised by difficulty defecating, infrequent bowel motions, and firm stool in youngsters. The majority of youngsters suffer from constipation due to either ingesting insufficient fibre and water, or due to their lifestyles having been disrupted. Sometimes, overzealous toilet training in infancy can be stressful for children, leading to chronic constipation later in life.